2006
DOI: 10.1021/ac0609935
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Quantitative Studies of Protein Immobilization Sites by Stable Isotope Labeling and Mass Spectrometry

Abstract: A method was developed for characterizing immobilization sites on a protein based on stable isotope labeling and MALDI-TOF mass spectrometry. The model for this work was human serum albumin (HSA) immobilized onto silica by the Schiff base method. The immobilized HSA was digested by various proteolytic enzymes in the presence of normal water, while soluble HSA was digested in 18 O-enriched water for use as an internal standard. These two digests were mixed and analyzed, with the 18 O/ 16 O ratio for each detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 42 publications
3
36
0
Order By: Relevance
“…Although free amine groups are involved in both the Schiff base immobilization method and glycation, these processes tend to involve different residues on HSA, making the resulting protein support a good model for the soluble forms of normal HSA or glycated HSA [26][27][28][29][30][31][32][33]48]. A control support was prepared in the same manner, but with no protein being added during the immobilization step.…”
Section: Preparation Of Supports and Columnsmentioning
confidence: 99%
“…Although free amine groups are involved in both the Schiff base immobilization method and glycation, these processes tend to involve different residues on HSA, making the resulting protein support a good model for the soluble forms of normal HSA or glycated HSA [26][27][28][29][30][31][32][33]48]. A control support was prepared in the same manner, but with no protein being added during the immobilization step.…”
Section: Preparation Of Supports and Columnsmentioning
confidence: 99%
“…Supports containing normal HSA or glycated HSA were immobilized to this support through the Schiff base method [56]. A previous study that determined which amine groups on HSA are involved in the Schiff base method has found that these residues tend to be different from those that are involved in glycation [57]. Control columns were prepared in the same manner but with no protein being added during the immobilization step.…”
Section: Methodsmentioning
confidence: 99%
“…As noted in prior work, the immobilization of HSA by this approach mainly occurs through the N -terminus or lysines that are not located at Sudlow sites I and II [37] and has been shown to provide columns with normal HSA or glycated HSA that are good models for the soluble forms of these proteins [10,18,21,22]. Control supports were prepared in the same manner but with no protein being added during the immobilization step.…”
Section: Methodsmentioning
confidence: 99%